Levonorgestrel Intrauterine System in Adjuvant Tamoxifen Treatment: Balance of Breast Risks and Endometrial Benefits—Systematic Review of Literature. (April 2014) - Gizzo, Salvatore; Di Gangi, Stefania; Bertocco, Anna; Noventa, Marco; Fagherazzi, Simone; Ancona, Emanuele; Saccardi, Carlo; Patrelli, Tito Silvio; D'Antona, Donato; Nardelli, Giovanni Battista
Levonorgestrel intrauterine system (LNG-IUS) is used in patients with breast patients taking tamoxifen (TAM) to prevent endometrial proliferation. The benefits (on endometrium), the side effects (on breast), and the patients suitable for this treatment are not still clear. Aim of this systematic review is to define the breast risks and endometrial benefits in TAM-treated women using Mirena and to define which patients could benefit from LNG-IUS use. In all, 3 studies on LNG-IUS effects on endometrium in TAM-treated women and 4 studies on breast cancer recurrence were selected for the study. All studies described a reduction in benign endometrial pathologies among Mirena users, but controversial data showed malignant disease and breast cancer recurrence. So it is mandatory to define hormonal status before TAM treatment. In selected patients Mirena was proven to protect endometrium. Perspective clinical trials on Mirena pharmacological features are necessary to establish whether systemic levels of progesterone could increase breast cancer recurrence in such patients.